(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Urinary bladder cancer is a disease of elderly and ranks 9th most common malignancy around the globe and 4th commonest in the men. In Pakistan it is the commonest urological malignancy and 4th commonest in men. Type of the tumor, grade and stage are important prognostic factors. The purpose of the study is to evaluate demography, types of the tumors along with grading and staging in patients presenting at a tertiary care teaching hospital. Patients and Methods: This was a descriptive cross-sectional study done at the Department of Pathology, King Edward Medical University, Lahore in collaboration with Urology Department of Mayo Hospital Lahore from January 2010 till December 2017. Total of 377 cases with diagnosis of urinary bladder cancer were studied. Demographic details, diagnosis, tumour grade and stage were evaluated. SPSS version 20 was used for data analysis. Descriptive analysis and results were tabulated as frequencies and percentages. The results were then compared with local and international studies. Results: Out of 377 cases of urinary bladder cancer, 319 were male and 59 were female (male to female ratio of 5.4:1) with mean age of 58.9±12.9 years. Transitional cell carcinoma comprised 92.3% of bladder cancer followed by squamous cell carcinoma (4%) and adenocarcinoma (2.4%). Majority of cancers were high grade (61%). Results of Stage PTa, PT1 and PT2 were 160 (42.4%), 56 (14.8%) and 161 (42.7%) respectively. High grade was associated with higher stage at diagnosis. Total of 41 (25.6%), 36 (64.3%) and 153 (95%) cases of high grade tumors were seen out of 160, 56 and 161 cases against PTa, PT1 and PT2 stages. Conclusion: Transitional cell carcinoma was the commonest malignant tumor among urinary bladder cancers followed by squamous cell carcinoma and adenocarcinoma. High grade cancer was the most common finding and was associated with advance stage of disease.